Effect of Re-etching of Oxalate-Occluded Dentin on Microleakage of Composite Resin Restorations - Aida Saffarpour; Maryam Ghavam; Kimiya Sadighi; Mohammad javad Kharazifard; Anna Saffarpour (Tehran University of Medical Sciences, 2016)
Objectives: This study aimed to assess the effect of re-etching of desensitized dentin for five and 10 seconds on marginal microleakage of composite restorations. Materials and Methods: Class V cavities (4x2x2mm) were prepared on the buccal surfaces of 64 third molars and randomly divided into four groups of 16. In the control group, Single Bond (SB) adhesive was applied after etching. In BB+SB group, after application of BisBlock (BB) desensitizer agent (which needs etching), SB adhesive was used. In BB+5E+SB group, re-etching of dentin was done for five seconds after application of desensitizer, and then the adhesive was applied. The process in BB+10E+SB was the same as BB+5E+SB group except for re-etching time, which was 10 seconds. The cavities were restored with composite resin. After 24 hours of storage in distilled water and 10,000 thermal cycles, all samples were subjected to dye penetration test. The teeth were sectioned buccolingually in the middle of restorations. A blind examiner observed the sections under a stereomicroscope. Results: At the occlusal margins, no significant difference in microleakage was observed among the groups (P>0.05). Application of BB in combination with SB had no effect in comparison to the control group (P>0.05); while there were significant differences in microleakage scores between BB+10E+SB and control (P=0.002), BB+10E+SB and BB+SB (P<0.001) and BB+5E+SB and BB+SB groups (P=0.009). Conclusions: Dentin re-etching after application of BB desensitizer increased the gingival microleakage of class V composite restorations. Application of BB desensitizer combined with SB adhesive enhanced marginal seal.